PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK), DANA BAGI HASIL (DBH) TERHADAP BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI PEMODERASI PADA KAB/KOTA PROVINSI JAWA TENGAH (PERIODE 2014-2016) - Muhammad Abdul Latif, 15.05.52.0342; Maryono, Maryono (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of Regional Original Income (PAD), General Allocation Funds (DAU), Special Allocation Funds (DAK), and Profit Sharing Funds (DBH) on Capital Expenditures which are moderated by Economic Growth. The population in this study is the Regency / City of Central Java Province which consists of 35 Regencies / Cities. This study uses secondary data in the form of the 2014 APBD Realization Report 2016. The data analysis technique used is multiple linear regression analysis.The results of this study indicate that Local Revenue (PAD), General Allocation Funds (DAU), Special Allocation Funds (DAK), Revenue Sharing Funds (DBH) have no effect on Capital Expenditures. While Economic Growth has been proven to moderate Regional Original Income (PAD) against Capital Expenditures. But Economic Growth does not moderate the relationship of General Allocation Funds (DAU), Special Allocation Funds (DAK) and Profit Sharing Funds (DBH) to Capital Expenditures.